Patriots [videorecording] - Hughes, Gruyneth; Welfare, Simon, Fairley, John (Red Empire presented by Robert Conquest ; series producer, Gruyneth Hughes, 1990)
Reflects confusion in the Soviet Union era whom the people should support in WW II, the Germans or the Nazi's however, Hitler forces their decision when he invades in 1941. The Nazis destroyed and defeated the Germans learning Joseph Stalin a hero. Includes liberation of Russian Red Army.